EFEK MEDIASI KEPUASAN KERJA DALAM KORELASI KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI DENGAN KINERJA GURU - Mariyono Mariyono; Supawi Pawenang; Bambang Mursito (JURNAL ILMIAH EDUNOMIKA, 2020)
The research is aimed to analyze the mediating effect of job satisfaction on the correlation of principals’ leadership and organization climate with the teachers’ performance. Survey research is employed among Junior High School teachers in Weru Sub District of Sukoharjo Municipality. The research was administered to 98 teachers from five school in the area. The research concluded that there were significant correlation between independent and dependent variables in the research both directly and indirectly. The research, therefore, showed that job satisfaction mediating the correlation of principals’ leadership and organization climate with the teachers’ performance. Key words: Teachers’ performance, principals’ leadership, organizational climate, job satisfaction.